Which types of aid have the most impact? - George Mavrotas (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2003)
The paper uses an aid disaggregation approach to examine the impact of different types of aid on the fiscal sector of the aid-recipient country. It uses time-series data on different types of aid (project aid, programme aid, technical assistance and food aid) for Uganda, an important aid recipient in recent years, to estimate a model of fiscal response in the presence of aid which combines aid disaggregation and endogenous aid. The empirical findings clearly suggest the importance of the above approach for delving deeper into aid effectiveness issues since different aid categories have different effects on key fiscal variables—an impact that could not be revealed if a single figure for aid was employed. More precisely, project aid and food aid appear to cause a reduction in public investment whereas programme aid and technical assistance are positively related to public investment. The same applies for government consumption. A negligible impact on government tax and non-tax revenues, and a strong displacement of government borrowing are also found.
Keywords: F35; 330; aid disaggregation; fiscal response; aid effectiveness; Uganda; Entwicklungshilfe; Theorie; Uganda